Fine mapping of the Hairy glume (Hg) gene in a chromosome variation region at the distal terminus of 1AS - Luo, Wei; Zhou, Jieguang; Liu, Jiajun; Liu, Yanlin; Mu, Yang; Tang, Huaping; Xu, Qiang; Deng, Mei; Jiang, Qiantao; Chen, Guoyue; Qi, Pengfei; Wang, Jirui; et al. (Frontiers in Plant Science, 2022)
Trichomes are differentiated epidermal cells and exist on above ground organs of nearly all land plants with important roles in resistance to a wide range of biotic and abiotic stresses. We attempted to obtain candidate gene(s) for Hairy glume (Hg), responsible for the trichome on wheat glume, by using bulked segregant exome capture sequencing (BSE-Seq), while Hg was only mapped in 0.52-3.26 Mb of 1AS. To further fine map this gene and identify candidate genes in this region, a near isogenic line-derived population consisting of 2,050 F2 lines was generated in the present study. By analyzing this population, Hg was fine mapped into a 0.90 cM region covering a physical distance of ~825.03 Kb encompassing 6 high- and 23 low-confidence genes in the reference genome of Chinese Spring. A presence-absence variation was identified in the fine mapping region through analyses of sequence-tagged sites markers and genome sequences of the hairy glume parent of the near isogenic lines. The results presented here will be useful for further cloning Hg in wheat.